Die kerk van die Woord - Boshoff, P. B. (Hervormde teologiese studies, 1995)
The church proclaiming the Word. The theme of the church is treated from the perspective of the theology of the Word. 1 Corinthians 5:19 is analyzed in the process. Divine revelation is discussed in the light of its being in the nature of an once-and-for-all event. This leads one to an understanding of the church in which the church best acquits itself of its task in public worship. The task of the church and the relationship between church and being a Christian are then considered.